Effects of vacation properties on local education budgets - Jason Giersch (Cogent Economics & Finance, 2014)
Residents of school districts with large percentages of vacation properties have the opportunity to export a portion of their school taxes onto the owners of those vacation properties. Those property owners are unlikely to consume educational services or have the opportunity to vote against local school taxes. Previous studies address exportation of taxes onto vacation property owners and the effects on local government budgets generally but not on education finances specifically. This study connects research on rates of vacation properties with that on local education finances by using data from the state of Georgia in 2010 and weighted least squares regression analysis to show that high percentages of vacation properties do indeed result in larger local school expenditures.
Keywords: 330; education finance; property taxes; local government